Anticancer half-sandwich Ir(iii) complex and its interaction with various biomolecules and their mixtures – a case study with ascorbic acid. Issue 15 (20th June 2022) - Masaryk, Lukáš; Orvoš, Jakub; Słoczyńska, Karolina; Herchel, Radovan; Moncol, Ján; Milde, David; Halaš, Petr; Křikavová, Radka; Koczurkiewicz-Adamczyk, Paulina; Pękala, Elżbieta; Fischer, Róbert; Šalitroš, Ivan; et al.
Abstract : An anticancer azo bond-containing half-sandwich Ir(iii ) complex oxidizes ascorbate to dehydroascorbate, and ascorbate recovers in the presence of reduced glutathione. Abstract : The extent of interactions with various biomolecules is a crucial feature of newly developed metallodrugs, worthy of thorough investigation, as its understanding helps uncover the fate of these xenobiotics in the physiological environment. In this work, promisingly cytotoxic half-sandwich complexes [Ru(η 6 -pcym)Cl(L 1 )]PF6 (1 ), [Ir(η 5 -Cp*)Cl(L 1 )]PF6 (2 ) and [Ir(η 5 -Cp*)Cl(L 2 )]PF6 (3 ), with 2-{ n -[( E )-phenyldiazenyl]pyridin-2-yl}-1 H -benzimidazole as a bidentate N-donor azo ligand ( n = 5 for L 1 and 6 for L 2 ; pcym = p -cymene, Cp* = pentamethylcyclopentadienyl), were subjected to an extensive and detailed study of interactions with a plethora of extra- and intracellular biologically relevant molecules. For the first time in the field of anticancer half-sandwich complexes, mixtures of 3 with ascorbic acid (ASA) and its combinations with reduced glutathione (GSH) and/or reduced nicotinamide adenine dinucleotide (NADH) were studied. Complex 3 undergoes azo bond reduction when mixed with NADH or ASA, which oxidizes to NAD + or dehydroascorbate (DHA), respectively. Intriguingly, the presence of the natural antioxidant ASA has a relevant prooxidative impact on GSH, which is connected with ASA recovery from DHA. Although the azo bond of L 2 involved in 3 seems to be the reaction centre for the dehydrogenation reactions of the biomolecules, L 2 by itself is a negligible oxidant and thus complexation in 3 represents a necessary prerequisite for the redox reactions.